1972
DOI: 10.1002/pol.1972.160100903
|View full text |Cite
|
Sign up to set email alerts
|

Side‐chain crystallinity. IV. Mechanical properties and transition temperatures of copolymers of methyl methacrylate with higher n‐alkyl acrylates and Nn‐alkylacrylamides

Abstract: SynopsisMechanical properties were correlated with glass transition temperatures for a series of random copolymers of methyl methacrylate with comonomers selected from the higher n-alkyl acrylates and N-n-alkylacrylamides. The plasticizing comonomers were the n-butyl, Zethylhexyl, n-octadecyl, and oleyl acrylates, and the N-n-butyl-, N-noctyl-, N-n-octadecyl-, and N-oleylacrylamides. The complete range of compositions was investigated. However, the bulk of the data was obtained on compositions in the glassy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…In general, this type of crystallization appears in atactic vinyl homopolymers having linear side groups with of 10 or more carbon atoms . Studies involving first‐order melting transitions of different functional polymers with regular side groups have been systematically reported in the last decades . Notably, side chain crystallizable polymers have been developed to control the release of a variety of active molecules in response to temperature changes.…”
Section: Resultsmentioning
confidence: 99%
“…In general, this type of crystallization appears in atactic vinyl homopolymers having linear side groups with of 10 or more carbon atoms . Studies involving first‐order melting transitions of different functional polymers with regular side groups have been systematically reported in the last decades . Notably, side chain crystallizable polymers have been developed to control the release of a variety of active molecules in response to temperature changes.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding was observed in Figure from the shift in the carbonyl resonance frequency as well as the disappearance of the isolated silanol peak. The effect of main chain mobility and structure on side chain crystallinity has also been extensively studied . It has been reported that chain stiffness retards the attainment of crystallinity .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of main chain mobility and structure on side chain crystallinity has also been extensively studied . It has been reported that chain stiffness retards the attainment of crystallinity . The retardation of crystallization was evident in the smallest adsorbed amount sample (0.74 mg/m 2 ) which showed effectively no crystallinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Furthermore, comb-like copolymers prepared by the copolymerization of long-chain monomers with common comonomers have been studied to improve solubility and to increase flexibility by internal plasticization. [9][10][11][12][13][14][15] and property of the copolymers. 1 7 -22 As a part of these studies, this paper deals with copolymerization parameters of isopropenyl-1,3,5-triazines containing long alkyl groups, and with the T 8 s and the side-chain crystallization of the resulting comb-like copolymers.…”
mentioning
confidence: 99%